Gunshot injury neck: an amazing case (Bangladesh Journal of Otorhinolaryngology, 2011)
Introduction: In this era use of firearms has become more prevalent in society. There is increase in numbers of firearm homicidal and suicidal victims. Injuries from gunshot wounds of head and neck vary in extant and significance, forming a spectrum from trivial to life threatening lesions. The head and neck have many vital structures confined to a small area of body, and hence in the event of head and neck trauma, there is greater potential of leading to a fatality. Case report: We report a case of homicidal gunshot injury (close range) sustained in the neck region, with the bullet having travelled through the neck without causing any mortality and little morbidity to the victim. Conclusion: Penetrating through and through, gunshot injury neck without causing any mortality and any significant morbidity is a very amazing incidence. Key words: Firearm; Gunshot; Bullet; Homicidal; Close range injury DOI: http://dx.doi.org/10.3329/bjo.v17i2.8857 BJO 2011; 17(2): 144-146